Research The Implementation of Basel III on The Financial Performance of The Banking Industry in Indonesia - Suryanto, Suryanto; Rasmini, Mas (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The 2008 global financial crisis prompted the Basel Committee to design the Basel III regulatory framework to strengthen capital and financial system resilience. Indonesia, as part of the global financial system, has also adopted Basel III since 2018, which directly impacts the structure and financial performance of national banking. This study aims to analyze the effect of Basel III implementation on the financial performance of banks in Indonesia, focusing on the indicators of Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Loan to Deposit Ratio (LDR). The research method used is a quantitative approach with panel data regression and validation using the Generalized Method of Moments (GMM) based on data from the 10 largest commercial banks from 2015 to 2024. The study results show that CAR has a positive and significant effect on ROA, while NPL has a negative effect, which is increasingly significant after being tested using GMM. The mean difference test also shows a significant increase in CAR after Basel III. While LDR has a positive effect, it is not significant. This study provides empirical evidence that the Basel III policy effectively improves the financial structure and increases the resilience of the national banking industry.  Keywords: Basel III; ROA; CAR; CAR; NPL; LDR